The Brazilian Constitution of 1988: a comparative appraisal - Alvarado, Arturo (Revista de Investigações Constitucionais, 2018)
This article examines the 1988 constitution of The Federative Republic of Brazil and its significance after 30 years of its implementation. Asserts some of its more advance social, political features and evaluates the current challenges to implement a democratic governance, based on a Rule of Law within the evolving constitutional framework. It also makes some comparisons between the Brazilian constitutional and political processes and other Latin American experiences, weighing whether or not Brazil started a new era of constitutional thinking in Latin America.